2019
DOI: 10.1007/s13318-019-00597-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Active Ingredients of Salvia miltiorrhiza and Carthamus tinctorius in Compatibility in Normal and Cerebral Ischemia Rats: A Comparative Study

Abstract: Background and Objective Dan-Hong injection, which comprises extracts of Salvia miltiorrhiza and Carthamus tinctorius, promotes blood circulation and reduces blood stasis. Combination of S. miltiorrhiza and C. tinctorius is more effective in treating cerebral ischemia than S. miltiorrhiza alone. This study aimed to examine the pharmacokinetic characteristics of four active ingredients of S. miltiorrhiza and C. tinctorius, namely danshensu (DSS), hydroxysafflor yellow A (HSYA), and salvianolic acid A (SAA) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The bimodal phenomenon of lithospermic acid and salvianolic acid A was observed in both the control and model groups treated with oral FS or FT. However, the results of others [ [35] , [36] , [37] , [38] , [39] ] showed that danshensu, lithospermic acid, and salvianolic acid A did not show a bimodal absorption phenomenon in rats. The bimodal phenomenon of caffeic acid was seen in the control group treated with oral FS or FT. Su's research results [ 40 ] showed that the drug time curve of caffeic acid in rats after oral administration of Shaofu Zhuyu decoction showed a bimodal phenomenon.…”
Section: Discussionmentioning
confidence: 90%
“…The bimodal phenomenon of lithospermic acid and salvianolic acid A was observed in both the control and model groups treated with oral FS or FT. However, the results of others [ [35] , [36] , [37] , [38] , [39] ] showed that danshensu, lithospermic acid, and salvianolic acid A did not show a bimodal absorption phenomenon in rats. The bimodal phenomenon of caffeic acid was seen in the control group treated with oral FS or FT. Su's research results [ 40 ] showed that the drug time curve of caffeic acid in rats after oral administration of Shaofu Zhuyu decoction showed a bimodal phenomenon.…”
Section: Discussionmentioning
confidence: 90%
“…Literature data report rat volume of distribution values of drugs ranging from 100 mL/kg to 100 L/kg orders of magnitude. Similarly, clearance values are reported ranging from 1 mL min -1  kg -1 to 10 L min -1  kg -1 orders of magnitude [52][53]. The pharmacokinetic data reported in Table 2 indicate, therefore, that the elimination rate of GER-UDCA from the rat bloodstream is relatively slow.…”
Section: A B C Dmentioning
confidence: 86%
“…In addition, S. miltiorrhiza can also lower blood sugar, regulate intracellular calcium ion concentration, inhibit inflammatory response, resist oxidation and scavenge oxygen free radicals together with other pharmacological effects (30)(31)(32)(33). Modern pharmacological studies have shown that S. miltiorrhiza can be used for the treatment of various diseases, including cerebrovascular disease (34,35), coronary heart disease (36,37), Parkinson's disease (38), Alzheimer's disease (39)(40)(41), peptic ulcers (42), scars (43), chronic kidney disease (44,45), liver cirrhosis (46), osteoporosis, lung cancer and other diseases (40). S. miltiorrhiza is one of the traditional Chinese medicines that can be used as a health food, as announced by the National Health Commission of China (47).…”
Section: Active Ingredients Of Salvia Miltiorrhizamentioning
confidence: 99%